Representações sociais da internação domiciliar na terminalidade: o olhar do cuidador familiar - Oliveira, Stefanie Griebeler (2010)
The present study aimed to identify social representations of home health care in the context of terminality on the perspective of the family caregiver. It is a qualitative research, and its participants were the family caregivers of the terminal oncologic patients who participated on the Home Health Care Service of University Hospital of Santa Maria (SIDHUSM) . The number of participants was determined by saturation criteria, totalizing 11 interviewed caregivers. Data collection was carried out through narrative interviews and simple observation. Data analysis was carried out through content analysis, considering the perspective of social representations theory. Ethical principles were respected, so that the participants rights were protected, as their participation was formalized through signing Informed Consent. Among the results, the family caregiver seemed to represent home health care as a way to easily access human and material resources, which are necessary concerning health care to be attained at home. Such way of health care also represents a health care team as reference, which, in a certain way, favors assistance throughout the urgent moments of terminality. It was evident that the caregivers understand home health care as beneficial for the patient, since it allows freedom and autonomy as regards meal times, hygiene, sleep, entertainment and visits. However, on the perspective of the family caregiver, home health care represents an overload, deprivation, greater responsibility, among other feelings, such as anguish and anxiety. Hospital, on the other hand, represents isolation for the patient, since it means restricted visiting hours, as well as lack of autonomy due to caregiving routines. Concerning the caregiver, hospital care represents freedom, since he can maintain his personal activities, concomitant with the feeling of being less responsible. It was possible to identify the importance of the nursing team, as regards the verification of the experience and readiness of the family caregiver to take this role, since many of them reported to feel anguish, not only caused by the diagnostic information of the patient, but also concerning the lack of preparation to take care of another person. Lack of autonomy is observed in some situations. The occultation of the diagnosis of terminality to the patient is something which happens quite often. Facing home health care of the terminal patient implies in seeing the human being degradation, enabling the emergence of several feelings as regards the family caregiver. In conclusion, it is relevant for the nursing team and the health care team, to understand and to know the social representations of home health care produced by family caregivers, since it may help on the approach and receptiveness towards them, who are suffering when receiving the diagnosis of terminality of their family member. Moreover, considering this study has demonstrated that home health care is represented by the family caregiver in its limitations, deprivation and challenges, it is urgent and emergent to come up with new ways to assist the family caregiver. Thus, the health care team may become a social support entity. Through listening, communication and enabling autonomy of the patient and his family it will be possible to accomplish a more holistic health care.